Pyrrole‐imidazole polyamide targeted to break fusion sites in TMPRSS2 and ERG gene fusion represses prostate tumor growth. Issue 10 (18th September 2014) - Obinata, Daisuke; Ito, Akiko; Fujiwara, Kyoko; Takayama, Ken‐Ichi; Ashikari, Daisaku; Murata, Yasutaka; Yamaguchi, Kenya; Urano, Tomohiko; Fujimura, Tetsuya; Fukuda, Noboru; Soma, Masayoshi; Watanabe, Takayoshi; et al.
<x xml:space="preserve">Abstract</x> Aberrant overexpression of ERG induced by the TMPRSS2‐ERG gene fusion is likely involved in the development of prostate cancer. Synthetic pyrrole–imidazole (PI) polyamides recognize and attach to the minor groove of DNA with high affinity and specificity. In the present study, we designed a PI polyamide targeting TMPRSS2‐ERG translocation breakpoints and assessed its effect on human prostate cancer cells. Our study identified that this PI polyamide repressed the cell and tumor growth of androgen‐sensitive LNCaP prostate cancer cells. Targeting of these breakpoint sequences by PI polyamides could be a novel approach for the treatment of prostate cancer.